The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/molecules23061318
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Evaluation of a New Series of Thiazole-Based Anticancer Agents as Potent Akt Inhibitors

Abstract: In an attempt to develop potent anticancer agents targeting Akt, new thiazole derivatives (1–10) were synthesized and investigated for their cytotoxic effects on A549 human lung adenocarcinoma, C6 rat glioma, and NIH/3T3 (healthy) mouse embryonic fibroblast cell lines. The most potent compounds were also investigated for their effects on apoptosis and Akt pathway. The most promising anticancer agent was found to be 2-[2-((4-(4-cyanophenoxy)phenyl)methylene)hydrazinyl]-4-(4-cyanophenyl)thiazole (6), due to its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…Furthermore, a molecular docking study was performed to analyze the interactions of RA and RAE in the active site of Akt. Homo sapiens Akt (PDB code: 4EJN) was chosen for docking studies according to report before [24]. The docked poses and docking interactions of RAE and RA in the active site of Akt are depicted in Figure 4B–E.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a molecular docking study was performed to analyze the interactions of RA and RAE in the active site of Akt. Homo sapiens Akt (PDB code: 4EJN) was chosen for docking studies according to report before [24]. The docked poses and docking interactions of RAE and RA in the active site of Akt are depicted in Figure 4B–E.…”
Section: Resultsmentioning
confidence: 99%
“…Based on Lipinski's rule of five, compound 99 was predicted as a potential orally bioavailable agent (Fig. 21) [112].…”
Section: Modification Of 2-amine To 2-hydrazonementioning
confidence: 99%
“…It has been revealed that compounds containing thiazole skeleton exhibit significant biological activities, which have pulled in consideration of researchers in both medicinal chemistry and chemical biology. In the domain of science, the thiazole skeleton is a key pharmacophore because of its ubiquity in a variety of biological properties . Few noteworthy examples of thiazole derivatives are depicted in Figure .…”
Section: Introductionmentioning
confidence: 99%
“…In the domain of science, the thiazole skeleton is a key pharmacophore because of its ubiquity in a variety of biological properties. [3][4][5][6][7][8][9][10] Few noteworthy examples of thiazole derivatives are depicted in Figure 1. Besides, the hydrazinylthiazolyl core is one of the important organic structures which have produced a profound interest in medicinal and industrial researchers.…”
Section: Introductionmentioning
confidence: 99%